2006
DOI: 10.1021/ja060036c
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of a Proline with Silaproline Causes a 20-Fold Increase in the Cellular Uptake of a Pro-Rich Peptide

Abstract: The results presented here show that elementary design enhancements have led to a 20-fold increase in the cellular uptake properties of a Pro-rich cell-penetrating peptide. These results are relevant not only due to the increasing interest in using CPPs as molecular shuttles for intracellular drug delivery but also because they illustrate the power of combining conformational analysis with rational design to modulate the behavior of biologically active compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 26 publications
(31 reference statements)
1
61
0
1
Order By: Relevance
“…In another study, cholesterol-derivatized oligonucleotides also showed a rapid binding and cytosolic partition in cells [62]. Closer to the CPP context, cell delivery improvement has been also observed upon stearylation of an octa-arginine peptide [63] or following the introduction of a proline amino acid derivative with a higher hydrophobicity into a prolinerich CPP [64]. In most of these studies, except for the last one, the derivatization of peptides with lipids was performed at the N-terminal end as it allowed easy coupling of the lipid by conventional amide bond formation directly on the peptidyl-resin after completion of the peptide sequence.…”
Section: Cpps and Cell Entrymentioning
confidence: 87%
“…In another study, cholesterol-derivatized oligonucleotides also showed a rapid binding and cytosolic partition in cells [62]. Closer to the CPP context, cell delivery improvement has been also observed upon stearylation of an octa-arginine peptide [63] or following the introduction of a proline amino acid derivative with a higher hydrophobicity into a prolinerich CPP [64]. In most of these studies, except for the last one, the derivatization of peptides with lipids was performed at the N-terminal end as it allowed easy coupling of the lipid by conventional amide bond formation directly on the peptidyl-resin after completion of the peptide sequence.…”
Section: Cpps and Cell Entrymentioning
confidence: 87%
“…Another promising SAP derivative is one in which a Pro of the hydrophobic face of the peptide is replaced by a Sip (g-(dimethylsila)-proline), providing a 20-fold increase in the cell uptake level. [19] In the present work, we set about answering the following questions: 1) Would an all-d version retain the cell-penetrating ability of SAP? ; and 2) Would an all-d version retain the noncytotoxicity of the original?…”
Section: Introductionmentioning
confidence: 99%
“…[9] In ar ecent study,t he a,a-disubstituted disilylated amino acid TESDpgw as synthesizeda nd incorporated into different positions in the antimicrobialp eptidea lamethicin. [10] The study showed that the a-helical structureo fa lamethicin was retained; however,t he antimicrobial activity against B. subtilis was lost for all the peptide analogues, possibly due to steric hindrance from the bulky amino acid preventing self-association of the peptideinthe membrane.…”
Section: Introductionmentioning
confidence: 99%